Periodontal Application of Manuka Honey: Antimicrobial and Demineralising Effects In Vitro - Safii, S.H.; Tompkins, G.R.; Duncan, W.J. (Hindawi Publishing Corporation, 2017)
Background. Topical application of manuka honey is effective in the treatment of burns and soft-tissue infections. The aim of this study was to assess the antibacterial activity of manuka honey against plaque-associated bacteria in vitro in order to evaluate the potential application as an adjunct to periodontal treatment. Materials and Methods. The minimum bacteriostatic and bactericidal concentrations (MIC and MBC) of manuka honey were compared to those of white clover honey against a variety of plaque-associated bacteria, at the natural and neutral pH. Dissolved calcium was measured following incubation of honeys with hydroxyapatite (HA) beads to assess their potential to demineralise oral hard tissues. Results. Both honeys inhibited most tested oral bacteria at similar MIC/MBC, but Streptococcus mutans was comparatively resistant. The honeys at pH neutral had little effect on antimicrobial activity. Incubation of HA beads in honey solutions resulted in pH-dependent calcium dissolution, and inoculation with S. mutans promoted further demineralisation by both types of honey. Conclusion. Manuka honey is antimicrobial towards representative oral bacteria. However, the relative resistance of S. mutans in association with the high concentrations of fermentable carbohydrates in honey and the direct demineralising effect at natural pH mitigate against the application of honey as an adjunct in the treatment of periodontal disease.